Foaming ceramic as well as preparation method and application thereof

By mixing powder or block-shaped colored glass frit with ceramic raw materials, foamed ceramics with uniform color or scattered color block distribution are prepared, which solves the problem of high difficulty in reducing colored materials and glazing in the prior art, and achieves stability Color and high-strength ceramic materials, suitable for architectural decoration.

CN119241273APending Publication Date: 2025-01-03JIANGXI SINOMA NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411384561.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The color materials of existing foamed ceramics are easily restored during firing, and cannot achieve the expected color effect. The glaze application process is difficult, the cost is high, and the glaze layer is easy to be damaged. It is difficult to maintain the color for a long time. It can only be colored on the surface, lacking internal uniformity. Color and stability.

Method used

Use powder or block-shaped colored glass frit as raw materials, and mix, granulate, stale and fire with ceramic raw material powder to give the foamed ceramic uniform color or scattered color block distribution, and use the coloring elements of the glass to protect the color material from being restored. , achieve uniform color effect from the inside to the outside.

Benefits of technology

It realizes the stable color effect of foamed ceramics, is not easy to damage, reduces the preparation cost, improves the compressive performance and strength of the material, and has the advantages of waterproofing, moisture-proofing, thermal insulation, and is suitable for the field of building decoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241273A_ABST
    Figure CN119241273A_ABST
Patent Text Reader

Abstract

The invention provides foamed ceramic as well as a preparation method and application thereof. The preparation method comprises the following steps: performing first mixing on ceramic raw material powder and a powdery colored glass material to obtain a mixture, performing granulation and aging on the mixture to obtain a first blank, firing the first blank, and cooling to obtain the foamed ceramic, or the ceramic raw material powder is granulated and aged and then secondarily mixed with the blocky colored glass material to obtain a second blank, and the second blank is fired and cooled to obtain the foamed ceramic. The preparation method can be used for preparing the colored foamed ceramic with long-term stable color aesthetic feeling, has the advantages of light weight, high strength, water resistance, moisture resistance, heat preservation and heat insulation, can be applied to the field of building decoration, has the advantages of simple steps, easily available raw materials, low cost and environmental protection, and can realize pollution-free treatment of colored waste glass and tailings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application belong to the field of inorganic materials, and in particular, relate to a foamed ceramic and a preparation method and application thereof. Background Art

[0002] Foamed ceramics are high-porosity closed-cell ceramic materials made from solid waste such as clay tailings as the main raw materials and fired at a high temperature of about 1200°C. Because of its advantages such as waterproof and moisture-proof, fire retardant, sound reduction, stable performance, high strength and light weight, it is a new type of green and environmentally friendly material with great potential, and is mostly used in the fields of building enclosures and decoration. In order to obtain better decorative appearance, it is currently common to add colorants to the raw materials or glaze the surface of foamed ceramics to make them present a colorful visual effect, but the colorants are easily reduced by a strong reducing atmosphere during the firing process and cannot achieve the expected color beauty; the glazing process is difficult and has a low yield, and can only be colored on the surface of the foamed ceramics, and there are problems such as thin glaze layer, easy damage and high cost. Therefore, it is necessary to provide a preparation method for colored foamed ceramics with excellent coloring effect, low cost and not easy to damage. Summary of the invention

[0003] In view of this, the present application provides a foamed ceramic and a preparation method thereof, which uses powdered colored glass or block colored glass as raw materials and utilizes its own coloring elements to give the foamed ceramic a uniform color from the inside to the outside, or a color effect with scattered color blocks distributed as a whole.

[0004] In a first aspect, the present application provides a method for preparing a foamed ceramic, comprising:

[0005] The ceramic raw material powder and the powdered colored glass material are first mixed to obtain a mixture, the mixture is granulated and aged to obtain a first blank, the first blank is fired and then cooled to obtain a foamed ceramic;

[0006] Alternatively, the ceramic raw material powder is granulated and aged, and then mixed with block colored glass material to obtain a second blank, and the second blank is fired and cooled to obtain a foamed ceramic.

[0007] Specifically, by weight, the first blank or the second blank includes 10-45 parts of tantalum-niobium tailings, 10-40 parts of lithium tailings, 3-10 parts of foamed ceramic waste, 10-50 parts of powdered colored glass or block colored glass, 1-8 parts of magnesia clay, 1-7 parts of potassium feldspar powder, 0.1-2 parts of silicon carbide and 0-1 parts of tripolyphosphate.

[0008] Specifically, the first mixing method is wet ball milling mixing, and the water content of the first blank is 5%-10% by weight.

[0009] Specifically, the second mixing method is dry mixing, the water content of the block colored glass material is 0.1%-1% by weight, and the water content of the second blank is 5%-10% by weight.

[0010] Specifically, the mixture is sieved through a 250-mesh sieve before granulation, and the residue is 0.4wt%-2.5wt%; the equivalent spherical diameter of the block colored glass material is 0.15mm-1mm.

[0011] Specifically, the granulation comprises preparing particles with a particle size of 150 μm-1000 μm by spray drying, and the aging is carried out at room temperature for a time of ≥ 3 days.

[0012] Specifically, the firing includes maintaining the temperature at 1080° C.-1140° C. for 1 h-3 h.

[0013] Specifically, the appearance of the foamed ceramic is uniformly colored, or distributed in scattered color blocks.

[0014] In a second aspect, the present application provides a foamed ceramic, which is prepared using the preparation method provided in the first aspect of the present application.

[0015] In a third aspect, the present application also provides the application of the foamed ceramics provided in the second aspect of the present application in the field of architectural decoration. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The foamed ceramic with uniform color appearance provided by Example 1 of the present invention;

[0017] Figure 2 This is a picture of a foamed ceramic with a scattered color block distribution appearance provided by Example 2 of the present invention. DETAILED DESCRIPTION

[0018] The following is a clear and complete description of the technical solutions and drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative motions are within the scope of protection of the present invention.

[0019] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commercially available products.

[0020] Equivalent spherical diameter: refers to the diameter of a sphere with the same volume as an irregular-shaped object.

[0021] Residue: The residue in this scheme refers to the mass percentage of the liquid slurry remaining on the sieve after being sieved on a standard sieve before granulation.

[0022] The color of foamed ceramics mainly comes from two aspects. On the one hand, coloring ingredients are added to the raw materials, including colorants and / or non-ferrous metals. For example, foamed ceramics with high iron content are gray-black, while those with iron content below 1% are gray-white. Different metal or metal salt contents will make them present different color effects. In order to obtain richer colors and better appearance decoration, on the one hand, foamed ceramics of different colors are often made by adding coloring pigments, and on the other hand, glaze slurry is applied to the surface of the formed ceramic body, and foamed ceramics with different glaze colors are obtained after integral firing. However, both coloring processes have their own problems. Foamed ceramics are fired in a strong reducing atmosphere, and many colorants are often reduced in a strong reducing atmosphere and fail to achieve the expected color; and because the formed ceramic body itself has various shapes and thicknesses, and each pore of the foamed ceramic material is an independent closed-cell form, it determines that its water absorption is low and the adsorption of glaze slurry is poor, resulting in greater difficulty in the glazing process, large glaze loss, and high cost. Moreover, it can only be colored on the surface of the ceramic, and its glaze layer is thin and easily damaged, making it difficult to maintain the original color effect for a long time.

[0023] In view of this, the embodiment of the present application provides a colored foamed ceramic and a preparation method thereof, using colored glass as raw material, using its own coloring elements to give the foamed ceramic a uniform color from the inside to the outside, or to make its appearance present a scattered color block distribution, and different colors of foamed ceramics can be obtained by selecting different colored glasses as needed, and the color effect of the foamed ceramics thus prepared is long-term stable and not easy to damage. And the waste recycled colored glass can be used as raw material, which has rich colors and wide sources, and can greatly reduce the preparation cost of the foamed ceramics, while being eco-friendly and reducing energy consumption.

[0024] The preparation method provided in the embodiment of the present application includes mixing the ceramic raw material powder with powdered colored glass material, and obtaining a foamed ceramic with uniform color through granulation, aging, firing, and cooling; or includes granulating and aging the ceramic raw material powder and mixing it with block-shaped colored glass material, and then firing and cooling to obtain a foamed ceramic with a scattered color block distribution.

[0025] The main components of glass are silicate complex salts Na2SiO3, K2SiO3, CaSiO3, and SiO2. It is an amorphous solid with no fixed melting point and irregular structure, usually colorless and transparent. It is often added with certain metal oxides or salts and colorants to the glass raw materials to make it present different colors. The metal can make the glass appear black, such as zirconium-gold, copper-red, nickel-yellow, cobalt-copper-blue, chromium-iron-green, and manganese-purple to obtain colored glass materials. Glass colorants include ionic colorants, compound colloidal colorants, and metal colloidal colorants. The firing process of foamed ceramics is often carried out in a strong reducing atmosphere, such as hydrogen and sulfur dioxide in the air. Colorants are directly added to the foamed ceramic raw materials to prepare colored foamed ceramics. Usually, these colorants will be reduced during the firing process and thus fail to achieve the expected coloring effect. Glass is a strong flux, and the silicon dioxide in it can achieve the state of silicon encapsulating the colorant, protecting the colorant in the glass from being reduced, so that the foamed ceramics can achieve the desired color effect. In addition, the introduction of colored glass materials into the foamed ceramic raw materials can not only give the foamed ceramics a stable color effect, but the glass microcrystals and / or bulk glass can also improve the vitrification degree of the foamed ceramics, play a skeleton support role, and enhance the compressive properties and strength of the foamed ceramics.

[0026] In one embodiment of the present application, a method for preparing a foamed ceramic comprises the following steps:

[0027] S101, mixing ceramic raw material powder and powdered colored glass material to obtain a mixture;

[0028] S102, granulating and aging the mixture obtained in step S101 to obtain a first blank;

[0029] S103, firing the first blank obtained in step S102, and cooling it to obtain a foamed ceramic.

[0030] The foamed ceramic prepared in one embodiment of this embodiment is a foamed ceramic with a uniform color appearance, such as Figure 1 shown.

[0031] In step S101, the ceramic raw material powder includes tantalum-niobium tailings, lithium tailings, foamed ceramic waste, potassium feldspar powder, silicon carbide, magnesia soil and tripolyphosphate. In parts by weight, the mixture includes 10-50 parts of powdered colored glass material, 15-35 parts of tantalum-niobium tailings, 10-40 parts of lithium tailings, 3-10 parts of foamed ceramic waste, 1-4 parts of potassium feldspar powder, 0.3-2 parts of silicon carbide, 1-5 parts of magnesia soil and 0-1 part of tripolyphosphate.

[0032] In the embodiments of the present application, the powdered colored glass material is a colored glass material in powder form. The powdered colored glass material may be glass waste, including one or more of silicate glass, borate glass, tempered glass, and soda-lime glass, and may be selected specifically according to color requirements. The powdered colored glass material may be a colored glass material including one or more colors, such as but not limited to one or more of red, orange, yellow, green, cyan, blue, and purple. The color of the foamed ceramic may come from a single colored glass material, or from a variety of colored glass materials, and the type and content of the colored glass material may also be adjusted to achieve foamed ceramics with a variety of color effects. In some embodiments of the present application, the weight percentages of the powdered colored glass material may be, for example, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, and 50 parts. If the content of colored glass is too low, the expected coloring effect cannot be achieved. If the content of colored glass is too high, the vitrification degree of the foamed ceramic will be too high, reducing its closed porosity and thus affecting the strength, thermal insulation and other properties.

[0033] In the implementation manner of the present application, the weight proportion of tantalum-niobium tailings can be, for example, but not limited to, 15 parts, 20 parts, 25 parts, 30 parts, 32 parts, and 35 parts; the weight proportion of lithium tailings can be, for example, but not limited to, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 38 parts, and 40 parts. On the one hand, the main components of tantalum-niobium tailings and lithium tailings are silicon dioxide and aluminum oxide, which play a skeletal support role in foamed ceramics, so that foamed ceramics have better mechanical properties, thermal properties and stability, and improve the service life and application range of foamed ceramics; on the other hand, tantalum-niobium tailings and lithium tailings are rich in feldspar and lithium mica, which can effectively reduce the firing temperature and facilitate low-temperature sintering, thereby saving energy; on the third hand, tantalum-niobium tailings and lithium tailings are used as raw materials to prepare green and environmentally friendly foamed ceramic products, which improves the utilization rate of tailings and reduces pollution to the environment.

[0034] In the embodiments of the present application, the foamed ceramic waste residue is used as a sintering aid to help the foamed ceramic obtain sufficient strength and accurate shape in the early stage of sintering. In some embodiments of the present application, the weight proportion of the foamed ceramic waste residue can be, for example, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, or 10 parts.

[0035] In the embodiments of the present application, potassium feldspar powder is also used as a sintering aid. Its main component is potassium-rich silicate mineral powder. It can act as a barren raw material before the ceramic is fired, reduce the drying shrinkage and deformation of the blank, improve the drying performance, and shorten the drying time. When firing the ceramic, it can be used as a flux to reduce the firing temperature and save heat consumption. In some embodiments of the present application, the weight proportion of potassium feldspar powder can be, for example, 1 part, 2 parts, 3 parts, or 4 parts.

[0036] In the embodiment of the present application, silicon carbide is used as a high-temperature foaming agent. During the high-temperature firing process, the main raw material of the ceramic reacts chemically with the foaming agent to generate a large amount of volatile gases. These gases will first cause the ceramic material to expand as a whole. Then, as the temperature decreases during the cooling process, the pores in the ceramic material after the gas evaporates are preserved, and a large number of dense closed pores are present inside the material, thereby obtaining foamed ceramics. Because each pore is in the form of an independent closed pore, it can effectively prevent the conduction and penetration of water and moisture, and at the same time can effectively isolate the external heat, and finally make the foamed ceramic have the characteristics of light weight, porous, waterproof, moisture-proof, and heat insulation. In some embodiments of the present application, the weight of silicon carbide can be, for example, 0.3 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, and 2 parts. If too little silicon carbide is added, the expected closed porosity will not be achieved, affecting the thermal insulation performance of the foamed ceramic; if too much silicon carbide is added, the closed porosity of the foamed ceramic will be too large, making it too loose and low in mechanical strength.

[0037] In the embodiments of the present application, the main components of the magnesia soil are silicon oxide, magnesium oxide and water, and its function is to stabilize the foam and assist the flux. In some embodiments of the present application, the weight proportion of the magnesia soil can be, for example, 1 part, 2 parts, 3 parts, 4 parts, or 5 parts.

[0038] In the embodiments of the present application, tripolyphosphate is used as a dispersant and a moisture retainer to improve the uniform dispersion of the components in the ceramic raw material mixture, which is beneficial to the uniform distribution of colored elements in the colored glass material, improves the uniformity of the structure and color of the foamed ceramic, and prevents water loss, thereby ensuring that the blank has a stable water content before firing, which is beneficial to the subsequent firing and molding. In some embodiments of the present application, the weight percentage of tripolyphosphate can be, for example, 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part.

[0039] In some embodiments of the present application, the first blank includes, by weight, 10-35 parts of powdered colored glass, 20-35 parts of tantalum-niobium tailings, 20-40 parts of lithium tailings, 5-10 parts of foamed ceramic waste, 2-4 parts of potassium feldspar powder, 0.3-0.5 parts of silicon carbide, 4-5 parts of magnesia clay and 0.2-0.6 parts of tripolyphosphate.

[0040] In the embodiment of the present application, the first mixing is wet ball milling mixing, the ball milling speed is 9r / min-16r / min, for example, it can be 9r / min, 10r / min, 11r / min, 12r / min, 13r / min, 14r / min, 15r / min, 16r / min; the ball milling time is 10h-20h, for example, it can be 10h, 12h, 12.5h, 14h, 16h, 18h, 20h. Water is added during the ball milling process, and the water plays a role in aiding the grinding of the material, which can not only make the powder materials of each component evenly distributed, but also further unify the powder particle size of the ceramic raw material powder and the powdered colored glass material, thereby improving the uniformity of the organization of the foamed ceramic.

[0041] In step S102, the mixture of ceramic raw material powder and powdered colored glass material forms a liquid slurry before granulation. The slurry needs to pass through a 250-mesh sieve, and the sieve residue is 0.4wt%-2.5wt%, for example, 0.4wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.5wt%, 1.8wt%, 2.0wt%, 2.3wt%, 2.5wt%. In some specific embodiments of the present application, the sieve residue of the liquid slurry after passing through a 250-mesh sieve before granulation is 1.0wt%-2.0wt%.

[0042] In the embodiment of the present application, granulation includes spray drying the liquid slurry of the mixture to obtain particles with a particle size of 150 μm-1000 μm. This process is to produce particles with uniform size and good fluidity to ensure that the ceramic body has good formability and mechanical strength during the subsequent firing process. In some embodiments of the present application, the particle size of the particles obtained after granulation can be, for example, 150 μm, 250 μm, 350 μm, 400 μm, 450 μm, 500 μm, 600 μm, 700 μm, 800 μm, 860 μm, 900 μm, 1000 μm. In some specific embodiments of the present application, the particle size of the particles obtained after granulation is 400 μm-900 μm.

[0043] In the implementation mode of the present application, aging includes placing the granules obtained by the above granulation in a room that is not transparent to sunlight and air for 3 days or more. This process is conducive to the hydrolysis and oxidation reaction of the ceramic blank, which can make the moisture in the blank more uniform, the blank particles are fully hydrated and ion exchanged, and some silicate minerals are hydrolyzed and transformed into clay substances after long-term contact with water, thereby improving the plasticity of the ceramic blank; the oxidation reaction can make the blank compact and uniform, reduce the chance of deformation during the firing process, and further improve the mechanical properties of the foamed ceramic blank. In addition, the aging process can effectively remove moisture and organic matter in the blank, reduce cracks and deformation during the firing process, and has a great effect on improving the appearance and performance of foamed ceramics, but the aging time is long to have a significant effect. In some implementation modes of the present application, the aging time can be, for example, 3 days, 4 days, and 5 days.

[0044] In an embodiment of the present application, the moisture content of the first blank obtained after the mixture is granulated and aged is 5-10%. If the moisture content in the blank is too high, a large amount of gas will be generated during the firing process, resulting in poor quality phenomena such as cracks and deformation inside the blank. In some embodiments of the present application, the moisture content of the first blank can be, for example, 5%, 6%, 7%, 7.8%, 8%, 9%, 10%. In some specific embodiments of the present application, the moisture content of the first blank is 6.5%-9.5%.

[0045] In step S103, the firing process is carried out in a kiln, which can be a natural gas tunnel kiln, a gas kiln, an electric kiln, a coal kiln, or a wood kiln. The firing temperature is 1080°C-1140°C, and the firing time is 1h-3h. In some embodiments of the present application, the firing temperature can be, for example, 1080°C, 1085°C, 1090°C, 1100°C, 1110°C, 1120°C, 1130°C, 1140°C; the firing time can be, for example, 1.0h, 1.5h, 1.75h, 2.0h, 2.5h, 3.0h. In some specific embodiments of the present application, the firing temperature is 1080°C-1095°C, and the firing time is 1.5h.

[0046] In the embodiment of the present application, the cooling process includes continuously introducing a volume flow rate of 20000m 3 / h~40000m 3 / h of cold air, the cold air volume flow rate can be, for example, 20000m 3 / h、25000m 3 / h、30000m 3 / h、32000m 3 / h、35000m 3 / h、40000m 3 / h. After a short circulation in the furnace, the cold air carries the heat and is discharged through the exhaust port. Since the foamed ceramic has strong self-insulation, it dissipates heat slowly after firing and curing, and has high requirements for the uniformity of heat dissipation on all surfaces. As a result, the natural cooling time accounts for more than 60% of the total preparation cycle of the foamed ceramic. Such a long preparation cycle is not suitable for industrial production. The purpose of introducing cold air is to speed up the cooling rate of high-temperature foamed ceramics, save time and cost, and improve the production efficiency of foamed ceramics. In some embodiments of the present application, the volume flow rate of the introduced cold air can be, for example, 25000m 3 / h-35000m 3 / h.

[0047] In another embodiment of the present application, a method for preparing a foamed ceramic comprises the following steps:

[0048] S201, granulating and aging the ceramic raw material powder to obtain green mud;

[0049] S202, mixing the blank obtained in step S201 with the block colored glass material to obtain a second blank;

[0050] S203, firing the second blank obtained in step S202, and cooling it to obtain a foamed ceramic.

[0051] The foamed ceramic prepared in one embodiment of this embodiment is a foamed ceramic with a uniform color appearance, such as Figure 2 shown.

[0052] In step S201, the ceramic raw material powder may be as described above, which will not be described again here.

[0053] In the implementation mode of the present application, the ceramic raw material powder is made into a liquid slurry before granulation, and the slurry needs to pass through a 250-mesh sieve, and the sieve residue is 0.4wt%-2.5wt%, for example, it can be 0.4wt%, 0.5wt%, 0.8wt%, 1.0wt%, 1.5wt%, 1.8wt%, 2.0wt%, 2.3wt%, 2.5wt%. In some specific implementation modes of the present application, the sieve residue of the liquid slurry after passing through a 250-mesh sieve before granulation is 1.0wt%-2.0wt%.

[0054] In the implementation manner of the present application, the specific operations of granulation and aging can be as described above, and will not be repeated here. The particle size of the particles obtained after granulation is 150μm-1000μm. In some implementation manners of the present application, the particle size of the particles obtained after granulation can be, for example, 150μm, 200μm, 300μm, 370μm, 420μm, 470μm, 550μm, 650μm, 750μm, 850μm, 950μm, 1000μm. In some specific implementation manners of the present application, the particle size of the particles obtained after granulation is 750μm-1000μm. The aging time can be greater than or equal to 3 days, for example 3 days, 3.5 days, 4 days, 5 days.

[0055] In step S202, the second blank includes, by weight, 10-50 parts of block colored glass material, 10-45 parts of tantalum-niobium tailings, 20-30 parts of lithium tailings, 3-10 parts of foamed ceramic waste, 2-7 parts of potassium feldspar powder, 0.1-1.7 parts of silicon carbide, 3-8 parts of magnesia clay and 0-0.8 parts of tripolyphosphate.

[0056] In the embodiment of the present application, the block colored glass material is a colored glass material in a block shape. The block colored glass material may be glass waste, including one or more of silicate glass, borate glass, tempered glass, potassium glass, and quartz glass. The block colored glass material may be a colored glass material including one or more colors, for example, but not limited to, one or more of red, orange, yellow, green, cyan, blue, and purple. The color of the foamed ceramic may come from a single colored glass material, or from a variety of colored glass materials, and the type and content of the colored glass material may be adjusted to achieve a foamed ceramic with a variety of color effects.

[0057] In the embodiments of the present application, the equivalent spherical diameter of the block colored glass material is 0.15mm-1mm. In some embodiments of the present application, the equivalent spherical diameter of the block colored glass material can be, for example, 0.15mm, 0.2mm, 0.3mm, 0.4mm, 0.5mm, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm.

[0058] In the implementation manner of the present application, the water content of the block colored glass block is 0.1%-1%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%. In some specific implementation manners of the present application, the water content of the block colored glass block is 0.4%-0.8%.

[0059] In the embodiment of the present application, the weight proportion of the block colored glass material can be, for example, 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts, 50 parts; the weight proportion of the tantalum-niobium tailings can be, for example, but not limited to, 10 parts, 14 parts, 18 parts, 22 parts, 26 parts, 33 parts, 40 parts, 45 parts; the weight proportion of the lithium tailings can be, for example, but not limited to, 20 parts, 24 parts, 26 parts, 28 parts, 30 parts; the weight proportion of the foamed ceramic waste slag can be, for example, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 30 parts; the weight proportion of the foamed ceramic waste slag can be, for example, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 8, 9, 10 parts; the weight of feldspar powder can be, for example, 2, 3, 4, 5, 6, 7 parts; the weight of silicon carbide can be, for example, 0.1, 0.3, 0.4, 0.5, 0.8, 1.1, 1.4, 1.7 parts; the weight of magnesia soil can be, for example, 3, 4, 5, 6, 7, 8 parts; the weight of tripolyphosphate can be, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 parts. The functions and beneficial effects of each component in the second blank refer to the description in the aforementioned step S101, which will not be repeated here.

[0060] In some embodiments of the present application, the second blank includes, by weight, 10-35 parts of bulk colored glass material, 20-40 parts of tantalum-niobium tailings, 20-30 parts of lithium tailings, 6-10 parts of foamed ceramic waste, 4-6 parts of potassium feldspar powder, 0.3-1 parts of silicon carbide, 3-7 parts of magnesia clay, and 0.5-0.8 parts of tripolyphosphate.

[0061] In the implementation manner of the present application, the second mixing is dry mixing.

[0062] In the implementation manner of the present application, the water content of the second blank is 5%-10% by weight, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%. The water content of the blank has a direct impact on its plasticity and drying shrinkage. The higher the water content, the more water is removed during the firing process, the greater the shrinkage, and the easier it is to generate internal stress and cause the blank to deform; but if the water content is too low, there is not enough water to evaporate during the high-temperature firing process, which will cause the blank to dry and crack. In some specific implementation manners of the present application, the water content of the second blank is 6%-8% by weight.

[0063] In step S203, the specific operations of firing and cooling may be as described above and will not be repeated here.

[0064] The preparation method of the foamed ceramic provided by the present application has simple steps, easy-to-obtain raw materials, low cost, green and environmentally friendly, and is suitable for industrial production. The present application uses the coloring elements of colored glass to give the foamed ceramic a uniform color from the inside to the outside or to make it present the appearance of scattered color blocks. Compared with the colored foamed ceramics prepared by glazing or colorant dyeing, the colored foamed ceramics provided by the present application have a very stable color aesthetic feeling, will not fade due to wear or over time, and have the advantages of light weight, high strength, waterproof, moisture-proof, and heat insulation. At the same time, its main raw materials are colored glass materials and tailings. The stockpile of tailings is large, and colored glass materials can be selected from waste glass. Therefore, the present preparation method turns waste into treasure, reduces the cost of raw materials, and also realizes the reuse of waste, relieves the pressure of recycling and processing of glass waste and tailings, and provides a new direction for its pollution-free treatment, with significant economic and social benefits and broad application prospects.

[0065] The present application also provides a foamed ceramic, which is prepared by the preparation method provided in the present application. The foamed ceramic has a uniform color or scattered color blocks in appearance, and the average pore size of the internal closed pores is 0.4mm-1.5mm, and the closed porosity is 65%-85%.

[0066] The present application also provides the application of the aforementioned foamed ceramics in the field of architectural decoration, including but not limited to being used as building exterior wall insulation panels, interior wall insulation panels, house partition panels, fire-resistant insulation decorative integrated panels, pipeline containers, and can also be used for water conservancy applications, road traffic, marine development, desert control, national defense construction, environmental protection, etc.

[0067] The technical solution of this application is further described below in multiple embodiments:

[0068] Example 1

[0069] A method for preparing a foamed ceramic, comprising:

[0070] (1) Ingredients: According to weight, weigh 15 parts of yellow powdered glass material, 32 parts of tantalum-niobium tailings, 38 parts of lithium tailings, 8 parts of foamed ceramic waste, 2 parts of potassium feldspar powder, 0.5 parts of silicon carbide, 4 parts of magnesia clay, and 0.5 parts of tripolyphosphate.

[0071] (2) Grinding, sieving and mixing: The components weighed in step (1) are crushed by a ball mill at a speed of 12 r / min for 12 h. The raw material powders are mixed by wet ball milling to obtain a mixture.

[0072] (3) Granulation and aging: The mixture obtained in step (2) is made into a liquid slurry and then passed through a 250-mesh sieve, with a sieve residue of 1.5 wt%; the sieved liquid slurry is spray-dried to obtain particles with a particle size of 860 μm. After aging at room temperature for 3 days, a green body is obtained, and the moisture content of the green body is 7.8% by weight.

[0073] (4) Firing and cooling: The blank obtained in step (3) is placed in a natural gas tunnel kiln for firing, heated to 1085°C and kept at this temperature for 1.75 hours. After firing, a volume flow rate of 30,000 m 3 / h of cold wind, and after cooling, take out the foamed ceramics, such as Figure 1 shown.

[0074] Example 2

[0075] A method for preparing a foamed ceramic, comprising:

[0076] (1) Ingredients: According to weight proportions, weigh 10 parts of black bulk glass material, 40 parts of tantalum-niobium tailings, 30 parts of lithium tailings, 10 parts of foamed ceramic waste, 6 parts of potassium feldspar powder, 0.4 parts of silicon carbide, 3 parts of magnesia clay, and 0.6 parts of tripolyphosphate, wherein the equivalent spherical diameter of the black bulk glass material is 0.6 mm, and the water content is 0.5%.

[0077] (2) Mixing, grinding and sieving: The raw materials except the black block glass material in step (1) are placed in a ball mill for mixing and grinding to obtain a mixed powder. The ball mill speed is 12 r / min and the ball milling time is 12.5 h.

[0078] (3) Granulation, aging, and blank making: the mixed powder obtained in step (2) is made into a liquid slurry and then passed through a 250-mesh sieve, with a sieve residue of 1.5 wt%. The sieved mixture slurry is spray-dried to obtain particles with a particle size of 950 μm; blank mud is obtained after aging at room temperature for 3.5 days; the blank mud is dry-mixed with the black block glass material weighed in step (1) to obtain a blank, wherein the moisture content of the blank is 7% by weight.

[0079] (4) Firing and cooling: The blanks are placed in a natural gas tunnel kiln for firing, heated to 1085°C and kept warm for 1.5 hours. After firing, a volume flow rate of 32,000 m 3 / h of cold wind, and after cooling, take out the foamed ceramics, such as Figure 2 shown.

[0080] Example 3

[0081] The only difference from Example 2 is that the weight portion of the black block glass frit is 15 parts.

[0082] Example 4

[0083] The only difference from Example 2 is that the weight portion of the black block glass frit is 20 parts.

[0084] Example 5

[0085] The only difference from Example 2 is that the weight fraction of the black block glass frit is 35 parts.

[0086] Example 6

[0087] The only difference from Example 2 is that the weight percentage of the black block glass frit is 40 parts.

[0088] Comparative Example 1

[0089] The only difference from Example 2 is that no black bulk glass frit is added.

[0090] The compressive strength of the foamed ceramics obtained in the examples and comparative examples was tested, and the results are shown in Table 1:

[0091] Table 1

[0092] serial number Powder / block glass frit weight Compressive strength / MPa Example 1 15 8.6 Example 2 10 8.4 Example 3 15 9.2 Example 4 20 9.6 Example 5 35 7.5 Example 6 40 5.2 Comparative Example 1 0 7.3

[0093] Example 1: A foamed ceramic prepared from yellow powdered glass as a raw material Figure 1 As shown, it is uniformly yellow in appearance.

[0094] Example 2-6 The foamed ceramic made from black block glass material has a scattered black block distribution in appearance. Figure 2 shown.

[0095] As can be seen from the above, Examples 1-6 give the foamed ceramics a uniform color effect from the inside to the outside by introducing powdered or block colored glass materials into the foamed ceramic raw materials. In addition, according to the test results in Table 1, the compressive strength of the foamed ceramics in Comparative Example 1, i.e., the raw materials without adding powdered or block colored glass materials, is 7.3Mpa, and the compressive strength of the foamed ceramics can be significantly improved after the introduction of powdered or block colored glass materials with a suitable content in Examples 1-4. It can also be seen from the results of Examples 1-4 that while keeping the types and contents of other raw materials of the foamed ceramics unchanged, the weight fraction of the block colored glass material is within the range of 10-20 parts, and the more the amount added, the better the compressive performance of the foamed ceramics finally obtained. Examples 5-6 indicate that after the number of block colored glass materials exceeds 35 parts, because the degree of vitrification is too high, the viscosity of the foamed ceramic blank gradually decreases, which will reduce the compressive strength of the foamed ceramics.

[0096] In summary, the foamed ceramic provided by the present application uses powdered colored glass material or block colored glass material as raw materials, which can not only make the appearance of the foamed ceramic present a uniform color or scattered color block distribution, thereby having good decorative properties, but also effectively enhance its compressive strength. In addition, the preparation method of the foamed ceramic provided by the present application not only ensures low cost but also realizes waste recycling, alleviates the pressure of recycling and processing of glass waste and tailings, is suitable for large-scale industrial production and has great environmental protection significance.

[0097] The above disclosure is only the preferred embodiment of the present application, and it cannot be used to limit the scope of the rights of the present invention. A person skilled in the art can understand that all or part of the processes of the above embodiments are implemented, and the equivalent changes made according to the claims of the present invention still fall within the scope of the invention. The above disclosure is only the preferred embodiment of the present application, and it cannot be used to limit the scope of the rights of the present invention. A person skilled in the art can understand that all or part of the processes of the above embodiments are implemented, and the equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A method for preparing a foamed ceramic, characterized in that: include: The ceramic raw material powder and the powdered colored glass material are first mixed to obtain a mixture, the mixture is granulated and aged to obtain a first blank, the first blank is fired and then cooled to obtain a foamed ceramic; Alternatively, the ceramic raw material powder is granulated and aged, and then mixed with block colored glass material to obtain a second blank, and the second blank is fired and then cooled to obtain a foamed ceramic.

2. The method for preparing the foamed ceramic according to claim 1, wherein: In terms of weight, the first blank and the second blank include 10-45 parts of tantalum-niobium tailings, 10-40 parts of lithium tailings, 3-10 parts of foamed ceramic waste, 10-50 parts of the powdered colored glass material or the block colored glass material, 1-8 parts of magnesia clay, 1-7 parts of potassium feldspar powder, 0.1-2 parts of silicon carbide and 0-1 parts of tripolyphosphate.

3. The method for preparing the foamed ceramic according to claim 1, wherein: The first mixing method is wet ball milling mixing, and the water content of the first blank is 5%-10% by weight.

4. The method for preparing the foamed ceramic according to claim 1, characterized in that: The second mixing method is dry mixing, the water content of the block colored glass material is 0.1%-1% by weight, and the water content of the second blank is 5%-10% by weight.

5. The method for preparing the foamed ceramic according to claim 1, characterized in that: The mixture is sieved through a 250-mesh sieve before granulation, and the residue is 0.4wt%-2.5wt%; the equivalent spherical diameter of the block colored glass material is 0.15mm-1mm.

6. The method for preparing the foamed ceramic according to claim 1, characterized in that: The granulation comprises preparing particles with a particle size of 150 μm-1000 μm by spray drying; and the aging is carried out at room temperature for a time of ≥3 days.

7. The method for preparing the foamed ceramic according to claim 1, characterized in that: The firing includes maintaining the temperature at 1080°C-1140°C for 1h-3h.

8. The method for preparing foamed ceramics according to claim 1, characterized in that: The foamed ceramic has a uniform color appearance or is distributed in scattered color blocks.

9. A foamed ceramic, characterized in that: The method is prepared by any one of claims 1 to 8.

10. Use of the foamed ceramic according to claim 9 in the field of architectural decoration.

Citation Information

Patent Citations

  • Tufa polished brick and manufacturing method thereof

    CN101407406A

  • Foamed ceramic and preparation method thereof

    CN111018491A

  • Production of foamed ceramic sheet

    JP1994116061A